Efecto del extracto de ajo (allium sativum) sobre la conservación del chorizo parrillero del cerdo criollo negro ibérico - Basurto Vera, Katherine Monserrate (2019)
The objective of this research was to evaluate the effect of garlic extract on the conservation of the chorizo sausage; in order to determine the final quality of the sausage. The factor under study were concentrations of 1%, 2%, 3%, 4%, 5% of garlic extract, a DCA was applied, with three replicates per treatment, for the analysis of the data was used Anova, Tukey test and Kruskall-Wallis at 0.05%. Physical-chemical parameters were evaluated: pH, acidity and humidity; microbiological: determination of Escherichia coli, Staphylococcus aureus, Salmonella, mesophilic aerobes; and sensory: flavor, color, smell, texture and acceptability. Based on the physico-chemical results, Dunnett was able to determine that T2 (1% garlic extract) was significant (p <0.05%) in the three variables studied (pH, acidity and humidity). Regarding microbiological analysis, total count of mesophilic aerobic bacteria are considered better concentrations 4 and 5% of garlic extract, since there was no microbial growth during the study days. All treatments were equal (p> 0.05%) for Escherichia coli, whereas for Staphylococcus aereus (p <0.05%) all treatments including the control, except for T4, were the best; Salmonella was total absence. Microbiologically all comply with the INEN standard (1338: 2012). Sensorially there was no consensus among tasters, probably because they were not trained.